Modernization of Pesantren and Graduate Quality - Ruhiyat, Ruhiyat; Didin Saepudin; Nirwan Syafrin; Budi Handrianto4 (Formosa Journal of Multidisciplinary Research, 2024)
Pesantren as an educational institution that produces human resources who have faith and the ability to implement knowledge as the quality of its graduates, needs to make adjustments to the times, both technologically and in terms of the quality of graduates. Pesantren graduates will be measured by their ability in the community to do something useful and felt directly in real terms. Therefore, pesantren should not close themselves off from the modern education system, but rather adapt to the existing and developing system to produce quality graduates. Along with the times, the requirements and indicators of quality graduates were born, this became a reference for pesantren to make changes to the education process, as well as changes in technology became a reference for pesantren to make changes to infrastructure facilities as a forum for developing the quality of graduates.